A rare cause of abdominal pain with fever - Oliveira, Diana Martins (BMJ Case Rep, 2019)
An 89-year-old man presented to the emergency department with a 1-month history of upper right quadrant pain, worsened in the last 3 days and accompanied by fever and chills. On physical examination, he had scleral icterus and right upper quadrant tenderness. Laboratory findings showed hyperbilirubinemia, elevated liver enzymes and C reactive protein. The patient was admitted, suspecting of an acute cholangitis and started on antibiotics. An upper gastrointestinal endoscopy revealed the presence of a juxtapapillary diverticulum in the second portion of the duodenum, which was confirmed by a magnetic resonance cholangiopancreatography, along with upstream biliary tract ectasia. The imaging findings allowed us to diagnose a Lemmel’s syndrome. Due to potential surgical risk, we decided for a conservative approach. The patient had a favourable course and was discharged home.